The law of workplace bullying (Champaign, IL, 2010)
"This issue brings together eight contributions from legal scholars and specialists in workplace bullying from four continents, who report on the state of the law governing a specific form of workplace abuse alternatively described as workplace bullying, psychological harassment, moral harassment, victimization, or mobbing."